2016
DOI: 10.1007/s00540-016-2270-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-axis out-of-plane versus long-axis in-plane ultrasound-guided radial arterial cannulation in adult patients: a randomized controlled trial

Abstract: The first-attempt cannulation success rate and cannulation time in adult patients are similar in ultrasound-guided radial artery cannulation with both short-axis as well as long-axis techniques. Trial registration Clinical Trial Registry of India (CTRI/2015/02/005552).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Three articles were excluded because the article type was a letter or meta-analysis. Ultimately, 11 studies 17 – 27 fulfilled the inclusion criteria for the meta-analysis ( Figure 1 ). The study characteristics are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three articles were excluded because the article type was a letter or meta-analysis. Ultimately, 11 studies 17 – 27 fulfilled the inclusion criteria for the meta-analysis ( Figure 1 ). The study characteristics are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analyses were performed to investigate the source of heterogeneity. In the radial artery (RA) subgroup, 19 , 21 , 26 , 27 the total success rate was no different between the SA-OOP and LA-IP groups (RR, 1.00; 95% CI, 0.96–1.05; P =0.88; I 2 =49%; Figure 3 ), and the TSA confirmed this result (the cumulative Z-curve crossed the futility boundary and entered the futility area; Figure 4A ). In the internal jugular vein (IJV) subgroup, 17 , 20 , 22 , 23 the total success rate was also no different between the SA-OOP and LA-IP groups (RR, 1.00; 95% CI, 0.98–1.02; P =0.99; I 2 =0%; Figure 3 ) and the TSA also confirmed the result (the cumulative Z-curve crossed the futility boundary and entered the futility area; Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Forest plot comparing the rate of first-attempt success (a) and total success (b) for ultrasound-guided versus palpation based on age vessel, collateral vasculature, and nervous structures with real-time guidance of catheter insertion for arterial catheterization. Controversy remains on which is better, the short-axis out-of-plane technique or the long-axis in-plane technique, for radial arterial catheterization [26,27]. Sethi et al [26] found that the identification of the midpoint of the radial artery on a short-axis view was probably easier with the out-of-plane technique.…”
Section: Discussionmentioning
confidence: 99%